KESELARASAN ALAM DALAM PENCITRAAN - Sukirno Sukirno (Gelar : Jurnal Seni Budaya, 2013)
Nature is one of Godâ€™s unique creations. Nature, with its perfect structure and balanced system, isable to maintain the continued survival of all creatures in the earth and to offer a variety of possiblecultivation for human welfare. On the other hand, nature also becomes the reference of people inresponding to life. Nature, with its phenomena, becomes an unwritten reference which can be readby anyone who is willing to read it. It is also true in the life of art that nature becomes the referenceand the source of inspiration in creating a work of art. Nature as manâ€™s environment is made useas a sery theme, espeeidlly when the destruction of nature and its environment is getting worse atpresent. Nature gradually sustdins destruction because of human behavior. Consequently, naturewhich should be a blessing turns to be a disaster for human beings. This could happen as theeffect of improper behavior of a creature named a man to his environment. The relation of natureto human beings presented above forms the principle of the idea in creating the painting entitledâ€œThe Harmony of Nature in lmageâ€ in the form of an interesting visual image which represents acertain meaning symbolically. The painting is visualized using kerok (scraping) technique andrefers to the combination of natural and expressive style although it seems to be decorativedepending on the idea so that an artistic, symbolic and representational form is created. Throughnew metaphors, the writer improvised innovatively based on the metaphors and then representedit in painting. In other words, the creation of the painting â€œThe Harmony of Nature in lmageâ€ is theresponse to the phenomenon of natural destruction existing in the writerâ€™s surroundings.